2022
DOI: 10.1542/peds.2021-052360
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Nafcillin for Empiric Therapy of Late-Onset Sepsis in the NICU

Abstract: BACKGROUND AND OBJECTIVE: In 2014 at Nationwide Children’s Hospital, the Neonatal Antimicrobial Stewardship Program recommended nafcillin over vancomycin for empirical therapy of possible late-onset sepsis (LOS) in infants without a history of methicillin-resistant Staphylococcus aureus colonization or infection. We report our experience with this guideline and assess its safety. METHODS: We retrospectively reviewed all infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…7,9 We observed MRSA bloodstream infections at a similarly low rate [3/250 (1.2%) LOS events] as others. 7,9 However, our guideline’s MRSI risk criteria failed to predict the single MRSA bacteremia among PostG infants. Case review revealed that a nasal MRSA screening had been negative 4 days before and positive 3 days after the sepsis evaluation.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…7,9 We observed MRSA bloodstream infections at a similarly low rate [3/250 (1.2%) LOS events] as others. 7,9 However, our guideline’s MRSI risk criteria failed to predict the single MRSA bacteremia among PostG infants. Case review revealed that a nasal MRSA screening had been negative 4 days before and positive 3 days after the sepsis evaluation.…”
Section: Discussionsupporting
confidence: 77%
“…Our experience aligns well with others' and highlights the usefulness of a multiprong approach to optimally reduce unnecessary neonatal vancomycin use. [5][6][7][8] Despite noted vancomycin reduction, guideline adherence was incomplete. Beside clinical decompensation/ill appearance, suspected NEC despite absent MRSI risk factors stood out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The input from the NEO-ASP during the study period informed practice and was a driving force responsible for its implementation and adherence. (24) The nding of only three positive bacterial blood cultures during the study period limits the safety of the intervention. However, the majority of antibiotic use in the NICU is in situations where the cultures are sterile and therein lies the relevance to every day NICU practice.…”
Section: Discussionmentioning
confidence: 99%